Implementation of the Prototyping Method for a Web-Based BUMDes Appakabaji Management Information System in Maros Regency - Nadin, Fauziah Rahma; Lilis Nur Hayati; Amaliah Faradibah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Operational management at the SPAM business unit of BUMDes Appakabaji is still carried out manually through visit records in books and has not yet been integrated into a digital system. As a result, data is difficult to trace and team work area distribution is not well organized. The growth in the number of customers, reaching 1,021 records, indicates the need for a more efficient management system. This study aims to develop a web-based management information system to improve the efficiency of customer data management, visit recording, work area mapping, payment management, and recapitulation reporting at BUMDes Appakabaji. The research employed the prototyping method, consisting of needs analysis, design, implementation, and testing stages. System testing using black box testing shows that the developed system functions properly and is feasible to improve operational efficiency.